Work design characteristics and knowledge sharing behavior among Software Engineers - Rehman, M. (Institute of Electrical and Electronics Engineers Inc., 2014)
Knowledge sharing is important for Software Engineers because software is purely based on individual's knowledge and one of the sources to learn new knowledge is through sharing. Although Software Engineering is a growing field, however research done in this profession is still not mature. One of the areas, which have not been thoroughly investigated in this profession, is working environment and its impact on knowledge sharing. Focus on this aspect of Software Engineering is important because work environment not only influences the performance of an individual but also the behavior (which in this case will be knowledge sharing behavior). Therefore, huge number of studies has been done conducted on designing work environment. One of the important works done was Job Characteristics Model (mostly used in Software Engineering field). However, it covers only five aspects of work/job. Therefore different other studies focused on more work design characteristics. This study analyzed the relationship between knowledge sharing behavior and work design characteristics among Software Engineers. Work design characteristics proposed by Morgeson and Humphrey (2006) were used for this study. This study was conducted in Malaysia and four locations were selected through geographical random cluster sampling. Results indicated that task identity, feedback from job, skill variety and received interdependence are the main work design characteristics for Software Engineers. Results also indicated that all work design characteristics has positive relationship with knowledge sharing behavior. Â© 2014 IEEE.